Resource mobilization and management for development - Fajingbesi, Adeyemi A.; Hiley, Mark.; Jalilian, Hossein (Ibadan, Nigeria : NCEMA, 1999)
Features extensive discussions of key issues in resource generation - human resources, taxation, capital accumulation, technological development and other yet untapped resources. It also covers different aspects of economic planning and advocates a redefinition of developmental goals, policy changes and adjustment in approaches to the utilization of resources for growth and development.
Includes bibliographical references and index.
oif 30/04/15
Loan
Keywords: Local government; Agriculture and state; Industrial policy; Developing countries; Nigeria